2020
DOI: 10.1021/acs.jmedchem.0c01609
|View full text |Cite
|
Sign up to set email alerts
|

Potent and Selective Mitogen-Activated Protein Kinase Kinase 1/2 (MEK1/2) Heterobifunctional Small-molecule Degraders

Abstract: Previously, we reported a first-in-class von Hippel–Lindau (VHL)-recruiting mitogen-activated protein kinase kinases 1 and 2 (MEK1/2) degrader, MS432. To date, only two MEK1/2 degrader papers have been published and very limited structure–activity relationships (SAR) have been reported. Here, we describe our extensive SAR studies exploring both von Hippel–Lindau (VHL) and cereblon (CRBN) E3 ligase ligands and a variety of linkers, which resulted in two novel, improved VHL-recruiting MEK1/2 degraders, 24 (MS928… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…4F ) improved the degradation efficiency, resulting in a greater reduction in BET proteins or CDK9 at lower concentrations of the PROTACs. Additionally, co-treatment of DLD-1 cells with FAK degrader (FAK-degrader-1) ( 29 ) or MEK1/2 degrader (MS432) ( 30 ) and tariquidar improved the protein reduction relative to single agent therapies ( Fig. S4E-F ), suggesting overexpression of MDR1 promotes resistance to degrader therapies, independent of protein target.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4F ) improved the degradation efficiency, resulting in a greater reduction in BET proteins or CDK9 at lower concentrations of the PROTACs. Additionally, co-treatment of DLD-1 cells with FAK degrader (FAK-degrader-1) ( 29 ) or MEK1/2 degrader (MS432) ( 30 ) and tariquidar improved the protein reduction relative to single agent therapies ( Fig. S4E-F ), suggesting overexpression of MDR1 promotes resistance to degrader therapies, independent of protein target.…”
Section: Resultsmentioning
confidence: 99%
“…K-ras mutations occur in nearly 40% of colorectal cancer (CRC) patients, supporting therapies that target K-ras effectors such as the MEK-ERK signaling pathway ( 35 ). Recently, MEK1/2 degraders have been developed that show potent anti-growth properties in RAS-RAF altered cancers ( 30 ). Notably, the majority of K-ras mutant CRC cell lines exhibit elevated ABCB1 expression ( 28 ), suggesting concomitant blockade of MDR1 may be required to achieve therapeutic efficacy with MEK1/2 degraders ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAC-1 has shown to directly activate procaspase-3 to caspase-3 and consequently induce MEK1/2 degradation. [57] In this article, the authors showed the combination effect of PAC-1 with In 2020, the same group reported the result of an extensive structure-activity relationship study of MS432 [53]. They optimized the types and length of the linkers to obtain two improved MEK1/2 PROTACs, MS928 and MS934 (Figure 10), by maintaining the MEK1/2 binder and VHL E3 ligase binder.…”
Section: Mek1/2 Degradermentioning
confidence: 98%
“…The use of MEK inhibitors is limited due to the acquired resistance towards them in patients undergoing long-term treatment. However, since mutations in MEK1/2 induce resistance to MEK inhibitors, the opportunity to overcome resistance should be investigated via MEK1/2 degradation and PROTAC technology [52][53][54].…”
Section: Mek1/2 Degradermentioning
confidence: 99%